Plan de calas de corcho y establecimiento de rodales selectos de alcornoque en andalucía - Carrasco, Angel; BORRERO, GUMERSINDO; CAMPAYO, P.; RODRIGUEZ, M.; ÁLVAREZ, J. Ma; FARIÑA, J. Ma; E. TORRES; Privado, Consultor; La, C. I.; Manojo, D. E. L.; Madrid, D. E. Rosas (II Congreso Forestal Español, 1997)
Since 1995, the "Consejería de Medio Ambiente" of the "Junta de Andalucía" has been developping a "Cork samples Plan and Establishment of select "Areas" of the Quercus suber". This plan is intended to collect technical-scientifical information, used both for a better knowledge of the cork oak forests and their principal product, cork, as well as for the elaboration of a cork quality map of the Andalusian Community. They also provide cork- tree owners with information about the explotation quality, for which cork samples are taken both from cork trees and from cork-piles. Using the collected samples, once they are classified and analised in the laboratory, and according to the data collected in the field, quality reports on cork are effec~ll(lted for the owner. Subsequently, these samples are show in a permanent exposition in thejaboratorywhere buyers or any other person interested can obtain information about the quality offered in the different Andalusian forests. Since 1995, the obtained information is also being used, amplifying the data taken referent to select "areas" of the cork oak forests to be able to establish a select "areas" network of Quercus suber capable of producing high quality acorns.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español
Keywords: Andalucía; Cork; cork-oak; Quercus suber; Select "areas"